Usability Analysis of Biometric Authentication Scheme for Smart Mobile Devices - M. Sujithra; G. Padmavathi (Innovations in Science and Technology Vol. 6, 2022)
Over the past few years, the usage of mobile devices to access data has becoming more frequent, and the usage of mobile devices in the applications such as web-browsing, email, multimedia, entertainment applications, navigation, trading stocks, electronic purchase, banking, and health care are increased, therefore data security is essential, and it becomes a challenge in securing the data in the mobile device. Over the years, criminals have learned to crack passwords and fabricate biometric traits and have conquered practically every kind of user-authentication mechanism designed to stop them from accessing device data. Stronger mobile authentication mechanisms are clearly needed. To address these problems in the mobile devices, biometric system can be developed which are more secure, affordable, and memorable authentication scheme based on graphical assistance, images, and audio. We believe that biometric authentication is the most secure approach among other authentication mechanism. It is preferred to apply biometrics for the security of Mobile devices and improve reliability. This paper discusses the various features of biometrics authentication schemes and mobile device security threats.